Dense and Cellular Zirconia Produced by Gel Casting with Agar: Preparation and High Temperature Characterization. (4th June 2013) - Tulliani, Jean-Marc; Bemporad, Edoardo; Sebastiani, Marco; Pulci, Giovanni; Tirillò, Jacopo; Bartuli, Cecilia
Abstract : A modified gel-casting process was developed to produce both dense and highly porous (40% volume) yttria tetragonal zirconia polycrystal (Y-TZP) using agar, a natural polysaccharide, as gelling agent. A fugitive phase, made of commercial polyethylene spheres, was added to the ceramic suspension before gelling to produce cellular ceramic structures. The characterization of the microstructural features of both dense and cellular ceramics was carried out by FEG SEM analysis of cross-sections produced by focused ion beam. The mechanical properties of the components were characterized at room temperature by nanoindentation tests in continuous stiffness measurement mode, by investigating the direct effect of the presence of residual microporosity. The presence of a diffuse residual microporosity from incomplete gel deaeration resulted in a decay of the bending strength and of the elastic modulus. The mechanical behavior of both dense and cellular zirconia (in terms of elastic modulus, flexural strength, and deformation at rupture) was investigated by performing four-point bending tests at the temperature of 1500°C.